Wpływ zmian w systemie dochodów jednostek samorządu terytorialnego na budżet powiatu grodzkiego na przykładzie miasta Łodzi - Bury, Agata (The Influence of Changes in a Local Self-Government Revenue System on the Budget of City with Local Government Administration Status on the Example Of Łódź, 2006)
The new act about finance of local self-government has obliged one year only. There are some new elements in governmental revenue system, for instance a new construction of general subsidy, new shares in the state budget taxes, and a new kind of revenue - like a "percentage" for executing of government administration tasks. Łódź is the second biggest city in Poland. The revenues are about 1.7 mid zł. The discussed act has not changed total revenues, but it has changed the structure. General subsidy was the main revenue of budget in 2003. Right now it has shares in state budget taxes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 614-623